PEMBANGKIT LISTRIK TENAGA GELOMBANG LAUT DENGAN MENGGUNAKAN TEKNOLOGI OSCILATING WATER COLUMN (OWC) DI PERAIRAN MARANA - Setiyawan, Setiyawan; Abdulrahim, N. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2021)
The alternatives to overcome electricity shortage in Indonesia is wave generating. One of the methods conducted in this research is OWC (Oscilating Water Column) based on study area criteria (Marana Village). OWC method can convert ocean wave energy atwave columnoscillationto generate electricity. To be able to produce electricity, this OWC device will train the wave energy through the OWC door hole. This research determine the amount of waves that can be utilized in Marana waters to be converted into units of electricity (watts). The amount of wave height that can be used, depends on the amount of wind that is in the waters of Marana. In addition to wave height, tidal is also needed to know the placement of Oscilating Water Column (OWC) is so that when the tidal water occurs, OWC is still in the condition of the wave. In addition, the bathymetry of the sea is also needed to know at the depth of how placed this OWC. Based on the results obtained from wave forecasting using the 2002-2006 wind data obtained maximum wave height for 5 years is 0.204 m in Year 2003. Which can generate electricity of 0.688 watts. Where from concluded in Marana waters do not have the potential to build Sea Wave Power Plant.